The Relationship Between Family Support and Family Stress in Pulmonary Tuberculosis Patients - Suarnianti, Suarnianti; Haskas, Yusran; BN, Indah Restika (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Pulmonary tuberculosis is the third most prevalent disease worldwide. It is a contagious disease caused by Mycobacterium tuberculosis, a bacterium characterized by dimensions of 0,5-4µ x 0,3-0,6µ and an outer thick layer composed of lipids that are resistant to chemical penetration. Family support is one of the factors influencing the treatment of pulmonary tuberculosis, where both main and extended family serve as a support system for their affected members. The primary function of a family is to provide healthcare. The objective of this study is to investigate the relationship between family support and family stress among pulmonary tuberculosis patients at Tamalanrea Primary Health Center. This study employed a quantitative cross-sectional research design and utilized a total sampling approach with a sample size of 32 patients. Data were collected through questionnaires and analyzed using Fisher’s Exact test. The results of the study revealed a significant relationship between family support and family stress in tuberculosis patients, with a p-value of 0,018. In conclusion, this study established a correlation between family support and family stress among pulmonary tuberculosis patients at Tamalanrea Primary Health Center. It is suggested that future researchers use larger sample sizes to explore additional factors that impact family support and family stress among tuberculosis patients.